Factors affecting the group formation, performance and continuity of multi-purpose cooperatives : case studies from Leyte, Philippines - Colis, Joan Carla F.; Weber, Karl E.; Dias, Hiran D.; Demaine, Harvey; Canadian International Development Agency (CIDA); Asian Institute of Technology-Canadian Universities Consortium Partnership Project (Bangkok : Asian Institute of Technology, 1993)
This study is primarily founded on a qualitative study of factors affecting group formation, performance, and continuity of groups in the two cooperatives of Hilongos Multi-Purpose Cooperative, Hilongos and San Isidro Parish Credit Cooperative, Inc., Inopacan, Leyte Province, Philippines. The group of the initiators and the followers are the two groups of samples set according to the stage in joining the cooperative. Data was obtained through individual interviews, related literature, and participant observation. The findings revealed that the factors affecting group formation are: 1) an organizing process which consist of the organizers, their roles and functions, the educational process; and 2) the interpersonal relations wherein the network of friends and kin exist. As for factors that enhance group performance and continuity, the results show that interpersonal relations and group competence, as a problem solving mechanism, are the important factors. Interpersonal relations include the awareness and participation of the members. Group competence can be manifest in the committee members of the cooperative playing significant roles in leadership. Furthermore, more focus is given to the group of the initiators than the group of the followers with regard to the three important factors which are the organizing process, interpersonal relations and group competence.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1993
Keywords: Consumer cooperatives -- Philippines -- Leyte